Characterisation of free and immobilised laccases from Ganoderma lucidum: application on bisphenol a degradation. Issue 1 (2nd January 2021) - Brugnari, Tatiane; Contato, Alex Graça; Pereira, Marita Gimenez; Freitas, Emanuelle Neiverth de; Bubna, Gisele Adriana; Aranha, Guilherme Mauro; Bracht, Adelar; Polizeli, Maria de Lourdes Teixeira de Moraes; Peralta, Rosane Marina
Abstract: Laccases (EC. 1.10.3.2) have a broad range of industrial applications. In order to overcome problems associated with loss of activity, storage and reusability of the free enzyme, a laccase from Ganoderma lucidum was immobilised successfully on monoaminoethyl-N-aminoethyl (MANAE)-agarose with high immobilisation yield and high activity recovery. The immobilisation improved significantly the thermal stability, with half-life 2.1- and 5.0-fold higher at 45 and 55 °C, respectively, in comparison with the free laccase. The storage stability at 4–8 °C of the immobilised laccase was also significantly higher than that the free form. Kinetic studies revealed that both free and immobilised G. lucidum laccases obeyed the Michaelis-Menten equation. Immobilisation increased Km and V max of the enzyme, reflecting a higher catalytic efficiency at high substrate concentrations. However, the V max / Km ratios were decreased by immobilisation, indicating a diminished catalytic efficiency at low substrate concentrations. The immobilised laccase was slightly more efficient than free laccase in the biodegradation of BPA. After 1 h, the immobilised laccase degraded 96.1 ± 3.0% of BPA at the initial concentration of 100 mg.L −1, whereas the free laccase removed 80.9 ± 3.5%. The immobilised G. lucidum laccase also efficiently degraded bisphenol A for at least 15 cycles of reuse.